TSADA - Sistema de telemetria redundante e tolerante a falhas utilizando tecnologia GSM/GPRS e Zigbee - Santos, Fernando Beux dos (2010)
This work deals with a telemetry system for agricultural mechanization, using GSM / GPRS and ZigBee Radio Frequency. The whole system is a mechanism for collecting and transmitting data at one point moving to a fixed basis, with a system integration and validation. The system gives priority to transmit GSM / GPRS, permitting as an alternative transmission over ZigBee, controlled common mechanism for failure detection, in case of loss of the GSM / GPRS connection the alternative transmission begins, as the system tries to establish a new connection with the priority transmission , thus making the transmission system redundant. The results were satisfactory as the system ensured the transmission of data with fault tolerance and redundantly in remote locations and different reliefs.